Evaluation of the Primary Pipe Network at Banua Anyar Booster Pump as an Effort to Reduce Water Loss in the Service area of Northern Banjarmasin, South Kalimantan - Hendra Arya Pratama; Eddy Setiadi Soedjono (Postgraduate School, Universitas Negeri Padang, 2023)
Recorded as the best PDAM in South Kalimantan in Banjarmasin City. PT. Bandarmasih Perseroda Drinking Water (PAM Bandarmasih) is still facing the problem of high water loss rates of 29.07% in 2022, which is still far above the National Medium Term Development Plan (RPJMN) target with a minimum water loss value of 20%. One of the ways PDAM can reduce water loss is by evaluating the pipe network in a District Meter Area (DMA). This research focuses on evaluating the primary pipe network in the area served by the Banua Anyar booster which serves 18 DMAs. Network evaluation using EPANET 2.0 software. The evaluation results show that the diameter of the primary pipe from the booster pump to the Banua Anyar pipe bridge has quite high unit-head loss and flow velocity values due to flow friction with the pipe surface. It is necessary to change the diameter of the primary pipe used in the Banua Anyar booster network from a diameter of 400 mm to 600 mm which can reduce the rate of water loss by 6.3%. In the future, it is hoped that the value of water loss at PDAM Banjarmasin City can be reduced and the affordability of drinking water services for the people of Banjarmasin City can increase.